YY1-induced long non-coding RNA small nucleolar RNA host gene 8 promotes the tumorigenesis of melanoma via the microRNA-656-3p/SERPINE1 mRNA binding protein 1 axis. Issue 3 (1st March 2022) - Shan, Baihui; Qu, Shengming; Lv, Sha; Fan, Dandan; Wang, Shu
ABSTRACT: Long non-coding (lnc) RNA serves a vital role in the cellular processes of carcinoma. This study aimed to explore the accurate mechanism underlying lncRNA small nucleolar RNA host gene 8 (SNHG8) in melanoma. In this study, lncRNA SNHG8 expression were upregulated in melanoma tissues and cells, and lncRNA SNHG8 knockdown reduced melanoma cell viability, migration and invasion. Moreover, lncRNA SNHG8 expression could be induced by transcription factor YY1. In addition, we found that miR-656 could directly bind to lncRNA SNHG8 and SERPINE1 mRNA binding protein 1 (SERBP1). Rescue assays indicated that miR-656 overexpression inhibited the aforementioned cellular activities in melanoma cells, which were reversed by SERBP1 overexpression. In conclusion, this work elucidated that YY1-induced upregulation of lncRNA SNHG8 boosted the development of melanoma via the miR-656-3p/SERBP1 axis, providing a novel therapeutic strategy for melanoma treatment. Graphical Abstract: uf0001